Perception of time throughout centuries - Einatyan, Julietta (History and Culture, 2025)
Time, along with space, is a form of existence of matter. It exists objectively and is indivisibly associated with moving matter.Starting from ancient times, astronomical phenomena created the basis for measuring Time. Computational methods of astronomy appeared in the second half of the 2nd millennium BC. Since the middle of the VIII century BC, mathematical astronomy has come a long way from prediction of eclipse dates with the use of lunar eclipse lists.
Keywords: Time; space; matter; nature; astrology; astronomy; Sun; Moon